Densities, excess volumes and partial molar volumes of lauryl methacrylate solutions in some organic solvents - Serheyev, Valentyn (Publishing House of Lviv Polytechnic National University, 2011)
Densities and excess volumes of the binary systems of lauryl (dodecyl) methacrylate with hexane, benzene, 1,2-diclorethane and acetic acid have been measured as a function of concentration, at 293 K and atmospheric pressure by pycnometric methods. The calculated excess volumes were approximated by polynomials. Визначено концентраційну залежність густини і надлишкового об'єму бінарних систем лаурил (додецил) метакрилату с гексаном, бензеном, 1,2-дихлоретаном і оцтовою кислотою при 293 K і атмосферному тиску, з використанням пікнометричного методу. Розраховані значення надлишкового об'єму були апроксимовані поліномами.
Густина, надлишковий об`єм і парціальні мольні об`єми розчинів лаурилметакрилату в деяких органічних розчинниках
Keywords: solutions; densities; excess volumes; lauryl methacrylate; hexane; benzene; 1,2-diclorethane; acetic acid; розчини; густина; надлишковий об'єм; лаурилметакрилат; гексан; бензен; 1,2-дихлоретан; оцтова кислота